Plant communities of the class Charetea Fukarek ex Krausch 1964 in Ukraine: an overview - Iakushenko, Dmytro; Borysova, Olena (Biodiversity: Research and Conservation, 2012)
The paper presents the results of the first syntaxonomical survey of the submerged plant communities belonging to the class of Charetea Fukarek ex Krausch 1964 in Ukraine based on the interpretation of about 80 published and unpublished phytosociological relevEs. Fourteen associations of two alliances and one order are characterized briefly. The diversity of charophyte communities in Ukraine is also described in brief. A preliminary prodromus of charophyte communities in Ukraine is given. Associations of Charetum intermediae (Corillion 1957) Fija≥kowski 1960, Charetum rudis Dπmbska 1966, Nitelletumgracilis Corillion 1957 are indicated for Ukraine for the first time.